“Creación de un sistema web con inteligencia artificial generativa para la creación de organizador gráfico, evaluaciones personalizadas y recomendaciones de recursos educativos” - Mera Carbo, Lister Leonardo (2024)
The use of technological tools and artificial intelligence (AI) in education is becoming indispensable in teaching and learning. Despite these advances, Ecuador still faces challenges in incorporating these technologies, especially in secondary education. This is due to the lack of preparation and adoption of intelligent tools that serve as support for both teachers and students. To address this lack of preparation and adoption of support tools for teachers and students, EduGeniusAi was developed, a web system that incorporates a generative AI model known as GPT-4. This intelligent web system will serve as a support tool for teachers in creating quizzes and for students in creating graphic organizers and accessing educational resources to reinforce their knowledge. Usability evaluations were carried out using the Post-Test usability technique and the SUS Questionnaire, resulting in an average of 79.8%. The conclusion drawn from the usability tests is that the web system is acceptable as a support tool for education in high school, both for teachers and students.